The natural history of the mud-dauber wasp Sceliphron fistularium (Hymenoptera: Sphecidae) in southeastern Brazil - Camillo, E.
(Es, En)
ilus., 19 ref.
Keywords: HYMENOPTERA; INSECTA; VESPIDAE; CICLO DE VIDA; PARASITOIDES; COSTA RICA